2016
DOI: 10.1080/21505594.2016.1247140
|View full text |Cite
|
Sign up to set email alerts
|

Fungi in the healthy human gastrointestinal tract

Abstract: Many species of fungi have been detected in the healthy human gut; however, nearly half of all taxa reported have only been found in one sample or one study. Fungi capable of growing in and colonizing the gut are limited to a small number of species, mostly Candida yeasts and yeasts in the family Dipodascaceae (Galactomyces, Geotrichum, Saprochaete). Malassezia and the filamentous fungus Cladosporium are potential colonizers; more work is needed to clarify their role. Other commonly-detected fungi come from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
323
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(381 citation statements)
references
References 70 publications
(63 reference statements)
13
323
3
5
Order By: Relevance
“…A recent review of 36 published gut mycobiota articles concluded that only 15 out of the 267 identified species were detected in more than 5 studies 33 . Among these 15 species, 13 can grow at 37°C and thus have the potential to permanently inhabit the intestinal niche 22,34 .…”
Section: Mycobiota At Steady State and In Dysbiosismentioning
confidence: 99%
“…A recent review of 36 published gut mycobiota articles concluded that only 15 out of the 267 identified species were detected in more than 5 studies 33 . Among these 15 species, 13 can grow at 37°C and thus have the potential to permanently inhabit the intestinal niche 22,34 .…”
Section: Mycobiota At Steady State and In Dysbiosismentioning
confidence: 99%
“…In most studies cataloging fungi found in the intestines of humans or mice, over 50 genera of fungi are commonly reported, although 10 or fewer typically account for vast majority of organisms detected [3,7]. The fungi most commonly reported in the intestines of mice and humans include Saccharomycetes including Candida and Saccharomyces spp., Eurotiomycetes including Aspergillus and Penicillium spp., Tremellomycetes including Cryptococcus and Trichosporon spp.…”
Section: Intestinal Fungal Microbiotamentioning
confidence: 99%
“…as well as Cladosporium , Wallemia , and Malassezia spp. [4,715]. Some reports also include robust detection of fungi such as Phoma , Alternaria , Sclerotinia and others which are primarily plant pathogens and are likely to be carried by food or other environmental sources.…”
Section: Intestinal Fungal Microbiotamentioning
confidence: 99%
“…Regarding the contrast between the conclusion of Chiaro’s study presenting S. cerevisiae as an important pathogen and scientific and clinical evidence gathered so far in basic and medical mycology, this lack of confirmation is not surprising. First, S. cerevisiae cannot be qualified as an “endosaprophyte”, which would mean that the normal condition of life for this species is the gut environment in which it is able to reproduce and disseminate[18]. This niche has been colonized by a limited number of fungal species which can survive and reproduce in the human gut environment, including Candida albicans and C. glabrata .…”
mentioning
confidence: 99%